2013
DOI: 10.1155/2013/952043
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Plant Calcium for Better Nutrition and Stress Tolerance

Abstract: External Ca2+ supplementation helps plants to recover from stress. This paper considers genetic methods for increasing Ca2+ to augment stress tolerance in plants and to increase their nutritional value. The transport of Ca2+ must be carefully controlled to minimize fluctuations in the cytosol while providing both structural support to new cell walls and membranes, and intracellular stores of Ca2+ for signaling. It is not clear how this is accomplished in meristems, which are remote from active transpiration—th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 238 publications
(346 reference statements)
0
14
0
Order By: Relevance
“…In addition, cax1/ cax3 double mutants displayed a severe reduction in growth, including leaf tip and flower necrosis and pronounced sensitivity to exogenous Ca 2+ and other ions (Cheng et al, 2005). In leaves, the vacuole serves as the reservoir for excess accumulation of Ca 2+ rather than the cell wall (Robertson, 2013). CAX1 keeps apoplastic Ca 2+ low through compartmentation into mesophyll vacuoles that is essential for normal plant function and productivity .…”
Section: Cax1 Vacuolar Antiporter Overexpression In Potato Results Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cax1/ cax3 double mutants displayed a severe reduction in growth, including leaf tip and flower necrosis and pronounced sensitivity to exogenous Ca 2+ and other ions (Cheng et al, 2005). In leaves, the vacuole serves as the reservoir for excess accumulation of Ca 2+ rather than the cell wall (Robertson, 2013). CAX1 keeps apoplastic Ca 2+ low through compartmentation into mesophyll vacuoles that is essential for normal plant function and productivity .…”
Section: Cax1 Vacuolar Antiporter Overexpression In Potato Results Inmentioning
confidence: 99%
“…The unbound extracellular Ca 2+ must be maintained in equilibrium across the apoplast-symplast boundary. In leaves, the vacuole serves as the reservoir for excess accumulation of Ca 2+ rather than the cell wall (Robertson, 2013). Park et al (2005a) transformed the potato cultivar 'Russet Norkotah' with a small version of CAX1 and reported that increased levels of CAX1 do not appear to alter potato growth and development, nor tuber morphology or yield.…”
Section: Cax1 Vacuolar Antiporter Overexpression In Potato Results Inmentioning
confidence: 99%
“…Following anaphase, a new cell wall is formed. During this process, Ca is very necessary to stabilize the developing cell wall by binding to pectate (Robertson, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…CAX1 has been recognized as a key regulator of apoplastic Ca 2+ concentrations, and its product maintains low apoplastic Ca 2+ levels via compartmentation into mesophyll vacuoles, which is essential for sufficient plant function and productivity (Conn et al, 2011). The vacuole is known to serve as the reservoir for excess accumulation of Ca 2+ (Robertson, 2013).The over-expression of sCAX1 in carrot (Park et al, 2004), tomato (Park et al, 2005a) and potato (Park et al, 2005b) has been shown to increase calcium contents in the edible parts of those species. Some studies showed that this over-expression can result in calcium deficiency symptoms such as blossom-end rot in tomato fruit (de Freitas et al, 2011) and leaf necrosis in tobacco (Hirschi, 1999).…”
Section: Introductionmentioning
confidence: 99%